UTJECAJ MOTORIČKIH SPOSOBNOSTI I KONATIVNIH REGULATIVNIH MEHANIZAMA NA SITUACIONO-MOTORIČKE SPOSOBNOSTI U KOŠARCI - Fuad Ražanica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The primar goal of this research was to establish the relationship between basic motoric abilities, conative regulatory mechanisms and effective success in situational-motoric tests of basketball. Therefore the group of 127 students, aged 15-17 was tested using twenty-four variables. Eight tests (complied with EUROFIT) were applied to evaluate motoric abilities. The following measuring instruments were chosen for evaluation of conative characteristics: Anxiety, Inhibitory conversion, Aggressivity and Schizoifrenic disorders Situational-motoric abilities in basketball were researched using the following tests: Throwing the ball against the wall using both hands, leading the ball in slalom and free throws. The regressive anlysis of criteria variable of the first main component of basketball elements gives enough information about the influence of applied motoric variables and variables of conative regulatory mechanisms on the success in performance of criteria variable treated.